Costa Recta beach, Deception Island, West Antarctica: A retreated scarp of a submarine fault? - Fernández-Ibáñez, Fermín; Pérez-López, Raul; Martínez Díaz, José Jesús; Paredes, Carlos; Giner Robles, Jorge Luis; T. Caselli, Alberto; Ibáñez, Jesús M. (Antarctic Science, 2005)
Received 3 August 2004 / Accepted 29 March 2005. © Antarctic Science Ltd. Contacto: fferiba@ugr.es. Deception Island (South Shetlands, Antarctica) is one of the most active volcanoes in Antarctica, having erupted recently in 1967, 1969 and 1970, damaging scientific stations on the island. It is also seismically very active. The island has attracted the attention of many researchers as it constitutes an undisturbed natural laboratory to study seismo-volcanic events and how they affect landscape modelling and evolution. One of the most remarkable geological and geomorphological features on Deception Island is the linearity of its easternmost coastal landform, the origin of which remains unknown. Some answers, based on presence of strike-slip fault or on the ice cap and beach geomorphological dynamics, have been reported in the literature. Our new work provides several indications of the existence of a dip-slip submarine fault, parallel to the coast (NNW–SSE), which suggests a tectonic origin for this morphological feature. Uplifted marine terraces, incision of a fluvial network over the ice cap, normal faulting parallel to the coast in the north and south rock heads bounding the beach and sharp shelf-break with rather constant slope, constitute some of this evidence. Terrace uplift and fluvial channel incision decreasing southward from Macaroni Point, indicates possible tilt movement across this inferred fault plane. Ministerio de Ciencia y Tecnología (España) Ministerio de Ciencia y Tecnología (España) Secretaría de Ciencia y Tecnología (Argentina) Depto. de Geodinámica, Estratigrafía y Paleontología Fac. de Ciencias Geológicas TRUE pub